X = { x_1,x_2,...,x_N }

Y = { y_1,y_2,...,y_N }

Z = { z_1,z_2,...,z_N }

Z(x) = 2*e(4x)

Z = { Z(x_1), Z(x_2),..., Z(x_N) }

sum(y) = 從 i=1 到 N 的總和，Y 組內的 y_i 值。

sum(z2) = 從 i=1 加總到 N，值 z_i2 在 設定的 Z 內。

sum2(x)= ( sum(x) )2

ln(x) = x 的自然對數

ln2(x) = ( ln(x) )2

Mean(X) = sum(x) / N

Mean(ln(x)) = sum( ln(x) ) / N

2005 以前的 Excel 版本

R2(Z,Y) = ( 2 N sum(yz) - N sum(z2) - sum2(y) ) / ( N sum(y2) - sum2(y) )

R2(Z,Y) = ( 2 N sum(ln(y) ln(z)) - N sum(ln2(z)) - sum2(ln(y)) ) / ( N sum(ln2(y)) - sum2(ln(y)) )

R2(Z,Y) = ( 2 N sum(yz) - N sum(z2) - sum2(y) ) / ( N sum(y2) - sum2(y) )

R2(Z,Y) = ( 2 N sum(ln(y) ln(z)) - N sum(ln2(z)) - sum2(ln(y)) ) / ( N sum(ln2(y)) - sum2(ln(y)) )

R2(Z,Y) = sum2( ( y - Mean(Y) )( z - Mean(Z) ) ) / ( sum( ( z - Mean(Z) )2 ) sum( ( y - Mean(Y) )2 ) )

R2(Z,Y) = sum(z2) / sum(y2

R2(Z,Y) = sum2( ( ln(y) - Mean(ln(y)) )( ln(z) - Mean(ln(z)) ) ) / ( sum( ( ln(z) - Mean(ln(z)) )2 ) sum( ( ln(y) - Mean(ln(y)) )2 ) )

R2(Z,Y) = sum( ln2(z) ) / sum( ln2(y) )

Excel 版本 2014 或更新版本

R2(Z,Y) = sum(z2) / sum(y2

R2(Z,Y) = sum2( ( y - Mean(Y) )( z - Mean(Z) ) ) / ( sum( ( z - Mean(Z) )2 ) sum( ( y - Mean(Y) )2 ) )